1991
DOI: 10.1111/j.1432-1033.1991.tb15937.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the gene for plant proliferating‐cell nuclear antigen and expression of this gene during the cell cycle in synchronized cultures of Catharanthus roseus cells

Abstract: A cDNA library was screened for plant proliferating-cell nuclear antigen (PCNA) from Catharanthus roseus (periwinkle). A 1 gtll cDNA library was constructed using poly(A)-rich RNA isolated from the cells in the S phase. A cDNA clone for PCNA was isolated by using a rice genomic clone, pCJ-1, which contains PCNA-related gene sequences. The cDNA contains an open reading frame of 804 nucleotides, encoding a protein of 268 amino acids with a molecular mass of 29765 Da. When conservative substitutions were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…After removal of propyzamide, cells immediately exited the M phase and the mitotic index dropped rapidly and remained at low levels until 12 h. A second peak of the mitotic index was observed from 12 to 16 h. In contrast, a peak in the DNA synthesis was observed at 9 h, after which the rate of DNA synthesis gradually decreased. We have chosen the PCNA gene as a control, since expression of the Catharanthus roseus PCNA gene was preferentially observed in the S phase [17]. Consistent with this observation, the tobacco PCNA gene was also accumulated predominantly during the late G1 and S phases (Fig.…”
Section: Expression Of Nte2f During the Cell Cyclementioning
confidence: 48%
“…After removal of propyzamide, cells immediately exited the M phase and the mitotic index dropped rapidly and remained at low levels until 12 h. A second peak of the mitotic index was observed from 12 to 16 h. In contrast, a peak in the DNA synthesis was observed at 9 h, after which the rate of DNA synthesis gradually decreased. We have chosen the PCNA gene as a control, since expression of the Catharanthus roseus PCNA gene was preferentially observed in the S phase [17]. Consistent with this observation, the tobacco PCNA gene was also accumulated predominantly during the late G1 and S phases (Fig.…”
Section: Expression Of Nte2f During the Cell Cyclementioning
confidence: 48%
“…Eight micrograms of total RNA were denatured and fractionated as described previously (Kodama et al, 1991). RNAs were blotted onto nylon membranes.…”
Section: Determination Of Levels Of Transcript Of the Fad7 Cenementioning
confidence: 99%
“…In higher plants, little is known about the cell cycle regulated genes and the mechanisms that regulate their transcription. We have previously isolated plant PCNA cDNA and demonstrated that the expression of the PCNA gene fluctuates during the cell cycle, with a peak during S phase, in synchronous cultures of Catharanthus roseus cells (Kodama et al 1991). Recently, S-phase specific expression of the ribonucleotide reductase gene has also been described (Philipps et al 1995).…”
Section: Discussionmentioning
confidence: 99%